Enantioseparation of 2‐(substituted phenyl)propanoic acids by high‐speed countercurrent chromatography and investigation of the influence of substituents in enantiorecognition. Issue 8 (29th March 2016) - Tong, Shengqiang; Wang, Xiaoping; Lu, Mengxia; Xiong, Qing; Wang, Qian; Yan, Jizhong
Abstract : This paper concentrates on the enantioseparation of racemic 2‐(substituted phenyl)propanoic acids by high‐speed countercurrent chromatography with substituted β‐cyclodextrin as the chiral selector, and an investigation of the influence of the substituent on the benzene ring in enantiorecognition between the chiral selector and enantiomer of each racemate is presented. This is an extension research of our previous work on the enantioseparation of 2‐phenyl propanoic acid derivatives, to investigate the relationship between the value of enantioseparation factor and the different substituent on the benzene ring. In total, ten racemic 2‐(substituted phenyl)propanoic acids were investigated, of which four including 2‐(4‐nitrophenyl)propanoic acid, 2‐(4‐methylphenyl)propanoic acid, 2‐(4‐hydroxyphenyl)propanoic acid, and 2‐(4‐chlorophenyl)propanoic acid, were studied by countercurrent chromatography for the first time, and two racemates were successfully enantioseparated. The distribution ratio and enantioseparation factor for all the ten racemates were determined by enantioselective liquid–liquid extraction. The results showed that an electron‐donating group on the benzene ring presents a higher enantiorecognition induced by chiral selector than that of racemates with an electron‐withdrawing group on the benzene ring.